The Effect of Quality, Quantity, Continuity, and Service of Sistem Penyediaan Air Minum (SPAM)/Drinking Water Supply System (DWSS) Products on Customer Satisfaction and Its Impact on Piped Water Absorption Using SEM-PLS Methods - Sarah Mulyani; Raras Herry K; Jerry Heikal (Publikasi Indonesia, 2026)
This study is intended to analyze the influence of quality, quantity, continuity, and service of Sistem Penyediaan Air Minum (SPAM)/Drinking Water Supply System (DWSS) products on customer satisfaction, which has an impact on the amount of piped water absorption. This study uses a quantitative approach with a survey method and Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were obtained through the distribution of questionnaires by the company’s QHSE Bureau to SPAM/DWSS customers, namely Perusahaan Daerah Air Minum (PDAM)/Drinking Water Regional Enterprise (DWRE). The respondents are PDAM/DWRE entities that have become partners of the company and cooperate in operating the water supply business. The variables studied include water quality (color, taste, odor, and pH), quantity (water capacity fulfillment and distribution), continuity (the ability to provide water at the required capacity and maintain its distribution processes), and service (ease of communication and responsiveness to the instructions given). The results of the study show that the X1 variable of product quality has a positive and significant influence on customer satisfaction, which also has a significant effect on the amount of piped water absorption. Product quality is the most dominant factor influencing satisfaction, and it increases the amount of piped water absorption. This indicates that customer considerations in SPAM/DWSS services are not only related to the quantity of water received and the consistency of distribution but also to the quality of the water consumed.